(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
The contribution, conceived within the Puppet & Design project, explores the possible implications of the multiple relations between the world of Puppets and the universe of Design, finding its main category in the concept and practices of ’animation’ trying to explore so many of the processes enacted by the case series of examples considered.